Cerebellar Pathology in Familial vs. Sporadic Essential Tremor - Louis, Elan D. (Cerebellum, 2017)
Familial and sporadic essential tremor (ET) cases differ in several respects. Whether they differ with respect to cerebellar pathologic changes has yet to be studied. We quantified a broad range of postmortem features (Purkinje cell (PC) counts, PC axonal torpedoes, a host of associated axonal changes, heterotopic PCs, and hairy basket ratings) in 60 ET cases and 30 controls. Familial ET was defined using both liberal criteria (n = 27) and conservative criteria (n = 20). When compared with controls, ETcases had lower PC counts, more torpedoes, more heterotopic PCs, a higher hairy basket rating, an increase in PC axonal collaterals, an increase in PC thickened axonal profiles, and an increase in PC axonal branching. Familial and sporadic ET had similar postmortem changes, with few exceptions, regardless of the definition criteria. The PC counts were marginally lower in familial than sporadic ET (respective p values = 0.059 [using liberal criteria] and 0.047 [using conservative criteria]). The PC thickened axonal profile count was marginally lower in familial ET than sporadic ET (respective p values = 0.037 [using liberal criteria] and 0.17 [using conservative criteria]), and the PC axonal branching count was marginally lower in familial than sporadic ET (respective p values = 0.045 [using liberal criteria] and 0.079 [using conservative criteria]). After correction for multiple comparisons, however, there were no significant differences. Overall, familial and sporadic ET cases share very similar cerebellar postmortem features. These data indicate that pathological changes in the cerebellum are a part of the pathophysiological cascade of events in both forms of ET.